Biomechanical interactions of Schistosoma mansoni eggs with vascular endothelial cells facilitate egg extravasation - Yi-Ting Yeh; Danielle E. Skinner; Ernesto Criado-Hidalgo; Natalie Shee Chen; Antoni Garcia-De Herreros; Nelly El-Sakkary; Lawrence Liu; Shun Zhang; Adithan Kandasamy; Shu Chien; Juan C. Lasheras; Juan C. del Álamo; et al. (PLoS Pathogens, 2022)
The eggs of the parasitic blood fluke, Schistosoma, are the main drivers of the chronic pathologies associated with schistosomiasis, a disease of poverty afflicting approximately 220 million people worldwide. Eggs laid by Schistosoma mansoni in the bloodstream of the host are encapsulated by vascular endothelial cells (VECs), the first step in the migration of the egg from the blood stream into the lumen of the gut and eventual exit from the body. The biomechanics associated with encapsulation and extravasation of the egg are poorly understood. We demonstrate that S. mansoni eggs induce VECs to form two types of membrane extensions during encapsulation; filopodia that probe eggshell surfaces and intercellular nanotubes that presumably facilitate VEC communication. Encapsulation efficiency, the number of filopodia and intercellular nanotubes, and the length of these structures depend on the egg’s vitality and, to a lesser degree, its maturation state. During encapsulation, live eggs induce VEC contractility and membranous structures formation in a Rho/ROCK pathway-dependent manner. Using elastic hydrogels embedded with fluorescent microbeads as substrates to culture VECs, live eggs induce VECs to exert significantly greater contractile forces during encapsulation than dead eggs, which leads to 3D deformations on both the VEC monolayer and the flexible substrate underneath. These significant mechanical deformations cause the VEC monolayer tension to fluctuate with the eventual rupture of VEC junctions, thus facilitating egg transit out of the blood vessel. Overall, our data on the mechanical interplay between host VECs and the schistosome egg improve our understanding of how this parasite manipulates its immediate environment to maintain disease transmission. Author summary Schistosomiasis, which infects over 200 million people, is a painful disease of poverty that is caused by inflammatory responses to the Schistosoma blood fluke’s eggs. To continue the parasite’s life cycle, eggs must escape the blood vessels and migrate through tissues of the host to the alimentary canal for exit into the environment. The biomechanical processes that help the immobile eggs to cross the blood vessel’s vascular endothelial cells (VECs) as the first step in this migration are not understood. We found that live but not dead eggs induce VECs to crawl over and encapsulate them. VECs in contact with live eggs make membranous extensions (filopodia) to explore the egg’s surface and also form long intercellular nanotubes to communicate with neighboring cells. VECs stimulate particular (Rho/ROCK) biochemical pathways to increase cell contractility and the forces generated are large enough to eventually break the junctions between cells and allow passage of the eggs into the underlying tissue. Our findings show how schistosome eggs activate and interact with VECs to initiate their escape from the bloodstream.